From Crash to Care: An Interdisciplinary Analysis of Road Traffic Accidents in Pakistan; Unifying Forensic Medicine and Public Health for Causes, Prevention and Emergency Response: Road Traffic Accidents in Pakistan: A Forensic–Public Health Analysis - Haq, Irshad Ul; Sana, Sanaila Gull; Syed, Sadia; Zaffar, Amna; Sabir, Samra; Khan, Younas (Pakistan Journal of Health Sciences, 2026)
Road traffic accidents (RTAs) are an emerging public health concern in Pakistan and have become a major cause of death and disability worldwide. The escalation in traffic-related injuries and fatalities has been mostly caused by rapid urbanization, inadequate emergency services, bad infrastructure, and a lack of enforcement of traffic laws. Objectives: To determine the primary causes and contributing elements of traffic accidents in Pakistan. Methods: Secondary data from the District Emergency Service, Rescue 1122, for the years 2022–2023, were used in a descriptive retrospective study design. Data on 12,407 victims of 8,170 RTAs were analyzed. Major risk trends were identified using descriptive and inferential statistics. Results: Almost over 50% of crashes involved motorbikes, with the most impacted age group being those between the ages of 21 and 30. The most common cause of death and disability was head injuries. The most frequent causes were driving underage and speeding. During the study period, 177 fatalities were reported. Conclusions: The results highlight how important it is to improve emergency systems, enforce traffic laws, and raise public awareness in order to reduce RTAs.